2006
DOI: 10.1504/ijep.2006.011222
|View full text |Cite
|
Sign up to set email alerts
|

Multiple criteria data envelopment analysis for full ranking units associated to environment impact assessment

Abstract: The importance of the environmental impact assessment (EIA) of large development projects is increasingly underlined. Usually, EIA involves a lot of qualitative and quantitative criteria. Data Envelopment Analysis (DEA), an effective method which is used to rank and select the best alternative from a set of alternatives, is not tailored to address qualitative criteria, thus rendering the application to multiple criteria problems not amenable. This paper presents a new methodology of Multiple Criteria Data Enve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 19 publications
0
46
0
3
Order By: Relevance
“…Although the mathematic expression of precipitation was mentioned a lot in this study, the analysis method was slightly old compared with the latest studies, especially the new methods in machine learning and neural networks [35][36][37][38][39][40], which should be strengthened in follow-up studies. The mechanism of ANPP response to precipitation fluctuation should be revealed more clearly in further studies.…”
Section: Discussionmentioning
confidence: 95%
“…Although the mathematic expression of precipitation was mentioned a lot in this study, the analysis method was slightly old compared with the latest studies, especially the new methods in machine learning and neural networks [35][36][37][38][39][40], which should be strengthened in follow-up studies. The mechanism of ANPP response to precipitation fluctuation should be revealed more clearly in further studies.…”
Section: Discussionmentioning
confidence: 95%
“…There have also been some recent studies using real-life case studies on sustainability elsewhere [16][17][18][19][20][21]. However, these previous studies are generally limited to a small region or to a prefecture, focused on a single or a few chemical elements.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical analysis also demonstrated that both socioeconomic transitions and physical environmental conditions are crucial determinants of shaping China's pollution and health maps. In particular, the double-edged effects of industrialization and urbanization reflected the multifactorial processes through which China's development and transitions fundamentally influenced human health with the degradation of the natural environment [34,40,59,72,73].…”
Section: Discussionmentioning
confidence: 99%